Karakteristik Pentakostalisme Menurut Kisah Para Rasul - Harls Evan R. Siahaan (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2017)
Abstract: Pentecostalism is often to be concerned with Holy Spirit baptism, Spiritual gifts or speaking in tongue. Basically, Pentecostalism is about to dynamize Christian life’s character. This article is aiming to refer the nature of Pentecostalism according to The Acts, that it is not only about speaking in tongue and other Spiritual gifts, but the characteristic. This article is a research that using text analyzis of The Book of Acts about the true charateristic of Pentecostalism. The conclusion of this biblical research is, pentecostalist characteristic is about building dynamic person who has such characters: continued steadfastly in fellowship and learning Bible, social care, enthusiastic, having favor with all the people, dare to witness, ministering with power and having intelegent ability.Abstrak: Fenomena Pentakosta sering hanya dikaitkan dengan persoalan baptisan Roh Kudus dan bahasa roh, bahkan juga dengan karunia Roh. Sejatinya, Pentakostalisme merupakan sebuah dinamisasi karakteristik kehidupan Kristen. Tulisan ini bertujuan untuk menunjukkan hakikat Pentakostalisme sesuai Kisah Para Rasul, bahwa Pentakostalisme bukan sekadar persoalan bahasa roh dan karunia roh yang lain, melainkan karakteristik. Penelitian ini bersifat analisis teks pada Kisah Para Rasul tentang karateristik Pentakostalisme yang sejati. Kesimpulannya, karakteristik pentakostalis adalah tentang membangun pribadi dinamis yang memiliki karakter: tekun bersekutu dan belajar firman, peduli sosial, antusias, disukai orang, berani bersaksi, melayani dengan kuasa dan memiliki kemampuan intelektualitas.